The impact of Malaysian industrial energy use in carbon dioxide emissions. - Abdullah Chik, Norlaila; Abdul Rahim, Khalid (2012)
This study attempts to identify the impact of Malaysia economy on CO2 emission by analyzing the energy intensity and CO2 emission intensity. Environment issues such as global warming and climate change give the negative effects to the Mother Nature such as floods, landslides, erosion and extremely heat. Otherwise, there is positive effect to the economy subsequent to disaster through the substitution of capital. Moreover, the government policy seen recently in the 10th Malaysian Plan will highly promote to energy efficiency and focus on high value added sector that produce less CO2 emission. This study found that Transportation sector has produced the highest value added with the highest CO2 emission. The finding of this study will facilitate energy policy makers to investigate the sector contributed high CO2 emission, and encouraged the high value added (productivity) sectors that produce less CO2 emission. Moreover, it is very important because recently the government, economist and policy makers have discussed the best strategies to protect the environment particularly in regarding to reduce the CO2 emission. From the finding, in order to reduce CO2 emission, the energy intensive sectors will also have to reduce energy consumption by applying the energy efficiency technology less CO2 technique in the future.